Proportionality and criminal law in the Interamerican-System - Clérico, Laura (Nomos Verlagsgesellschaft mbH und Co KG, 2023)
This essay aims to explore the uses of proportionality when criminal law interferes with human rights in Latin America. To do so, I use the case law of the Interamerican Court of Human Rights ("IACtHR") as an exemplary basis to demonstrate the various uses of proportionality, to focus on its use in challenging criminal law and criminal sanctions. As I will show, the proportionality test is a methodology that forms part of the consolidated jurisprudence of the IACtHR and this has relevance for the Inter-American system because of the impact that the Court's standards seek to have at the domestic level.
CRIS-Team Scopus Importer:2024-12-16